A new Cyrtoneuropsis Malloch from Brazil (Diptera, Muscidae) - Márcia S. Couri; Viviane Rodrigues de Sousa (Revista Brasileira de Entomologia, 2011)
A new Cyrtoneuropsis Malloch from Brazil (Diptera, Muscidae). This paper presents the description of a new species of Cyrtoneuropsis Malloch from São Carlos, São Paulo providing illustrations of the male and female terminalia and with a brief discussion on its systematic position within the genus.